PENGARUH KOMPENSASI BONUS DAN LEVERAGE TERHADAP MANAJEMEN LABA YANG DIMODERASI OLEH VARIABEL UKURAN PERUSAHAAN - Pangaribuan, David; Rely, Gilbert; Aditia, Dimas (Fakultas Ekonomi dan Bisnis Universitas Katolik Indonesia Atma Jaya, 2023)
This study aims to analyze and test empirically the effect of bonus compensation, leverage and moderating company size on earnings management practices in Food and Beverage Sub-Sector Companies Listed on the Indonesia Stock Exchange Period 2018 – 2021). This research is a quantitative research using purposive sampling with 45 samples. The results of the study show that bonus compensation, leverage and firm size have a positive effect on earnings management. Furthermore, company size moderates Bonus Compensation and leverage on earnings management. Suggestions for future research need to link earnings management practices with good governance, profitability, and audit quality and expand the research sample using a cross section or time series with a longer time horizon.